Peritoneal Dialysis for Acute Kidney Injury - Brett Cullis; Mohamed Abdelraheem; Georgi Abrahams; André Luís Balbi; Dinna N. Cruz; Yaacov Frishberg; Vera Hermina Kalika Koch; Mignon McCulloch; Alp Numanoğlu; Peter Nourse; Roberto Pecoits–Filho; Daniela Ponce; et al. (2014)
ispd guidelines